2021
DOI: 10.1021/acssuschemeng.0c08599
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Extraction of Biomass—A Green and Sustainable Method to Control the Pyrolysis Product Distribution

Abstract: This research demonstrates that supercritical extraction of the biomass has a remarkable and complex influence on Scots pine tree fractions changing the surface concentration of water, lipids, and metals simultaneously. Surprisingly, this surface composition modification makes a considerable impact on the pyrolysis of the bulk biomass mechanism, leading to the alternation of the volatile and inorganic matter composition. The unique combination of time-of-flight secondary-ion mass spectrometry analysis and util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…ScCO 2 extraction has been reported as an alternative method of pretreatment prior to enzymatic or thermochemical processes, as it increased the permeability of the biomass surface and inuences the surface composition of elements, which leads to improved downstream processing. 19,48 Previous studies have demonstrated a decrease in surface metal ion concentrations for K + and Na + , in addition to Ca + , Mg + , Al + , and Si + post scCO 2 extraction of Scots pine tree fractions. 19 SEM results indicated that ScCO 2 extraction demonstrated a high efficiency and selectivity to remove valuable phytochemicals without leaving any solvent residue in the rice straw.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…ScCO 2 extraction has been reported as an alternative method of pretreatment prior to enzymatic or thermochemical processes, as it increased the permeability of the biomass surface and inuences the surface composition of elements, which leads to improved downstream processing. 19,48 Previous studies have demonstrated a decrease in surface metal ion concentrations for K + and Na + , in addition to Ca + , Mg + , Al + , and Si + post scCO 2 extraction of Scots pine tree fractions. 19 SEM results indicated that ScCO 2 extraction demonstrated a high efficiency and selectivity to remove valuable phytochemicals without leaving any solvent residue in the rice straw.…”
Section: Resultsmentioning
confidence: 98%
“…19,48 Previous studies have demonstrated a decrease in surface metal ion concentrations for K + and Na + , in addition to Ca + , Mg + , Al + , and Si + post scCO 2 extraction of Scots pine tree fractions. 19 SEM results indicated that ScCO 2 extraction demonstrated a high efficiency and selectivity to remove valuable phytochemicals without leaving any solvent residue in the rice straw. Therefore, the extracted straw is suitable for further uses in various applications.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, due to the stirring effect of the device and the collision of SHC, the surface of the peanut shells was partially broken after desiccation. Compared to extraction, the internal pore channels of peanut shells were exposed, increasing the contact area between the peanut shell fuel and oxygen during subsequent combustion . For biomass with poor thermal conductivity like peanut shells, the rough surface could not only increase the mass transfer in the combustion process but also facilitate the liberation of volatiles …”
Section: Resultsmentioning
confidence: 99%
“…Also, the contents of aromatics increased at first and later decreased with the increase in pyrolysis temperature. Tubetskaya et al 18 identified that the inorganic contents such as metals found in biomass can act as catalysts for the pyrolysis process, thus influencing the product distribution. It can be inferred that there is an apparent increase in the inorganic content after each step of staged pyrolysis, implying that the subsequent processes can yield high-quality and stable bio-oils.…”
Section: Introductionmentioning
confidence: 99%